Konsep Perancangan Pusat Kuliner dan Oleh-Oleh Di Kota Kediri, Jawa Timur dengan Tema Arsitektur Ikonik - Ilham Gusti Syahadat; Agus Wiryadhi Saidi; Siluh Putu Natha Primadewi (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
Culinary and Souvenir Center in Kediri City is an effort made to utilize the local Culinary and Souvenirs with their uniqueness in each region are a local potential. Various efforts can be made to develop this potential, one of which is by building facilities that concentrate the buying and selling activities of typical products. The design of the Culinary and Souvenir Center in Kediri City is an effort to utilize local attractions and address the need for iconic tourism-supporting facilities in Kediri City. The purpose of this design is to provide a solution to these problems, including design specifications, basic concepts, and design concepts of the Culinary and Souvenir Center in Kediri City. This study uses a descriptive analytical approach with data collection methods using observation techniques and literature studies. The design results of the Culinary and Souvenir Center in Kediri City refer to the basic commercial and recreational concepts with an iconic architectural theme that is in line with the function of this facility. The total area of ​​​​the room in this facility is 10,551 m2 and is built on a land area of ​​​​13,940 m2 located on Jalan Suparjan Mangun Wijaya, Kediri City. The design of this facility takes into account the design concepts that have been prepared, namely the site design concept, building design concept, structure and material concept and utility concept.